PENERAPAN ARSITEKTUR ISLAM PADA RANCANGAN RUMAH SAKIT ISLAM GORONTALO - Ilham Mu'ani; Zuhriati A. Djailani; Niniek Pratiwi (Universitas Negeri Gorontalo, 2023)
ABSTRACT. Gorontalo Islamic Hospital is a type D general hospital as part of a social organization located on Jalan Prof. HB. Jassin in Gorontalo City. This hospital serves patients both from Gorontalo City and from outside of it. However, the current hospital facilities are inadequate, particularly for inpatient facilities, both in terms of buildings and indoor facilities. According to one of the hospital staff/employees, several buildings are old, one of which is the inpatient building, so leaks often occur when raining. Additionally, many other problems emerge, such as the absence of parking facilities, narrow and hot emergency rooms, too narrow circulation among buildings/corridors, absence of eye care and hemodialysis facilities, and often clogged drains. In reference to these problems, it is indispensable to redesign the Gorontalo Islamic Hospital using a quantitative method based on measurement results in the form of standard results for room size and hospital capacity. Also, it employs qualitative methods in the form of words that contain meaning, instead of numbers, esppecially in the form of any theory or information, standard hospital room facilities, hospital room activities, and room function requirements. The Gorontalo Islamic Hospital was redesigned by directed it to the concept of Islamic Architecture, which employed three principles, including Habluminallah (the human relationship with Allah SWT), Habluminannas (the human relationship with fellow human beings) and Habluminal'alam (the human relationship with nature). The application of Islamic Architecture was also Motivated by the fact that it was in accordance with the Vision of the Gorontalo Islamic Hospital, namely